Hester Prynne and Ethan Frome: Two Faces of the Same Tragedy (Journal of the College of Basic Education, 2022)
Human tragedy is characterized by its continuity over and over in human history. Many writers elaborate different tragedies, each according his\her own experience and understanding of world tragedies. The present study shows a comparison of such tragedies between two novels; one by Nathaniel Hawthorne's Scarlet Letter and the other by Edith Wharton's Ethan From. The study sheds light on the way each novelist presents different sorts of human agony, the points they meet and the points they differ.Both Nathaniel Hawthorne's (1804-64) Scarlet Letter (1850) and Edith Wharton's (1862–1937) Ethan Frome (1911) are compelling classics of American literature with characters trapped in tragic circumstances they seem unable to escape. Remarkably, the two novels represent turning points in the lives of their authors. Whereas his previous work suffered from popular indifference, Hawthorne's Scarlet Letter gained him the attention he had formerly lacked, no small part of it negative. Actually a conservative in many regards, with the publication of The Scarlet Letter, Hawthorne became viewed as a radical and a subversive by conservative reviewers. (Bloom, Bloom’s Classic Critical Views, p. 1) At the same time, Wharton's Ethan Forme has long held a canonical place as the most artistically perfect and formally accomplished of her fictions. (Lawson, 154) Moreover, both novels are based on real incidents. In his introduction to The Scarlet Letter "The Custom House", Hawthorne reports how he discovered by accident a decayed, embroidered "A" and some documents telling of its history and the story of one Hester Prynne: [T]he object that most drew my attention to the mysterious package was a certain affair of fine red cloth, much worn and faded, There were traces about it of gold embroidery, which, however, was greatly frayed and defaced, so that none, or very little, of the glitter was left. (SL, "The Custom House", p. 20).